Highly effective B@g-C3N4/polyaniline nanoblend for photoelectrocatalytic reduction of CO2 to methanol - Tarek, Mostafa; Atta, Mahmoud; Muhd Zahiruddin, Shukor; Hamidah, Abdullah; Khan, Md Maksudur Rahman (Wiley-VCH Verlag, 2023)
Photoelectrocatalytic (PEC) conversion of CO2 has been extensively investigated as it uses solar energy to combine CO2 and water to produce hydrocarbons. In the present work, B@graphitic carbon nitride (g-C3N4)/polyaniline (PANI) nanoblend was synthesized by in situ polymerization of aniline in the presence of B@g-C3N4 for PEC CO2 reduction. The catalyst was characterized by field emission scanning electron microscopy (FESEM), transmission electron microscopy, X-ray diffraction, UV-Vis absorption spectroscopy, photoluminescence, X-ray photoelectron spectroscopy (XPS), and Mott-Schottky analysis. The PEC activity was evaluated by linear sweep voltammetry (LSV) and chronoamperometry. XRD revealed the formation of g-C3N4, while B doping was confirmed by XPS. The presence of PANI was visualized by FESEM. A remarkable cathodic current associated with CO2 reduction was observed during LSV from an onset potential of –0.01 V vs. normal hydrogen electrode (NHE), which is more positive than that of B@g-C3N4 (–0.82 V vs. NHE), and the positive shift is attributed to the slow charge recombination kinetics of B@g-C3N4/PANI as evidenced by PL results. The mechanism of PEC CO2 reduction was investigated and discussed on the basis of the Mott-Schottky results. In conclusion, B@g-C3N4/PANI opens a new avenue to develop photoelectrocatalysts for PEC CO2 reduction to methanol.